Electron Acceptor Availability Shapes Anaerobically Methane Oxidizing Archaea (ANME) Communities in South Georgia Sediments - Schnakenberg, Annika; Aromokeye, David A.; Kulkarni, Ajinkya; Maier, Lisa; Wunder, Lea C.; Richter-Heitmann, Tim; Pape, Thomas; Ristova, Petra Pop; Bühring, Solveig I.; Dohrmann, Ingrid; Bohrmann, Gerhard; Kasten, Sabine; et al. (Frontiers in Microbiology, 2021)
Anaerobic methane oxidizing archaea (ANME) mediate anaerobic oxidation of methane (AOM) in marine sediments and are therefore important for controlling atmospheric methane concentrations in the water column and ultimately the atmosphere. Numerous previous studies have revealed that AOM is coupled to the reduction of different electron acceptors such as sulfate, nitrate/nitrite or Fe(III)/Mn(IV). However, the influence of electron acceptor availability on the in situ ANME community composition in sediments remains largely unknown. Here, we investigated the electron acceptor availability and compared the microbial in situ communities of three methane-rich locations offshore the sub-Antarctic island South Georgia, by Illumina sequencing and qPCR of mcrA genes. The methanic zone (MZ) sediments of Royal Trough and Church Trough comprised high sulfide concentrations of up to 4 and 19 mM, respectively. In contrast, those of the Cumberland Bay fjord accounted for relatively high concentrations of dissolved iron (up to 186 μM). Whereas the ANME community in the sulfidic sites Church Trough and Royal Trough mainly comprised members of the ANME-1 clade, the order-level clade “ANME-1-related” (Lever and Teske, 2015) was most abundant in the iron-rich site in Cumberland Bay fjord, indicating that the availability of electron acceptors has a strong selective effect on the ANME community. This study shows that potential electron acceptors for methane oxidation may serve as environmental filters to select for the ANME community composition and adds to a better understanding of the global importance of AOM.